2018
DOI: 10.1002/jmv.25022
|View full text |Cite
|
Sign up to set email alerts
|

Virological patterns of HCV patients with failure to interferon‐free regimens

Abstract: The study characterized the virological patterns and the resistance-associated substitutions (RASs) in patients with failure to IFN-free regimens enrolled in the real-life setting. All 87 consecutive HCV patients with failed IFN-free regimens, observed at the laboratory of the University of Campania, were enrolled. All patients had been treated with DAA regimens according to the HCV genotype, international guidelines, and local availability. Sanger sequencing of NS3, NS5A, and NS5B regions was performed at fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…Moreover, our population was at low probability of re‐infection, since the presumed duration of HCV infection was very long (at least 12 years). Instead, patient #6 harboured different HCV 1 subgenotypes (1b and 1a respectively) before the start of the DAA regimen and at relapse; therefore, in this case, we can hypothesize a re‐infection with another subgenotype of HCV, although an erroneous identification of the HCV subgenotype before the start of DAA may also be possible …”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Moreover, our population was at low probability of re‐infection, since the presumed duration of HCV infection was very long (at least 12 years). Instead, patient #6 harboured different HCV 1 subgenotypes (1b and 1a respectively) before the start of the DAA regimen and at relapse; therefore, in this case, we can hypothesize a re‐infection with another subgenotype of HCV, although an erroneous identification of the HCV subgenotype before the start of DAA may also be possible …”
Section: Discussionmentioning
confidence: 91%
“…Instead, patient #6 harboured different HCV 1 subgenotypes (1b and 1a respectively) before the start of the DAA regimen and at relapse; therefore, in this case, we can hypothesize a re-infection with another subgenotype of HCV, although an erroneous identification of the HCV subgenotype before the start of DAA may also be possible. 17 The clinical significance of a late relapse remains unclear; it suggested that some patients thought to have achieved an SVR may still harbour HCV. In some studies, despite serum HCV-RNA negativity after interferon treatment, patients may occasionally present low levels of detectable virus in the liver tissue during a follow-up period of 1-2 years after the end of treatment, 30,31 a condition that has been demonstrated to be a predictor of a later recurrence of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These NS5A RASs could be found at different levels of a mixed population of the mutated and wild-type viruses[ 21 , 22 ]. In NS5A inhibitor-experienced patients, especially those who have undergone a complete course of 12-wk or > 12-wk treatment, DAA-selected NS5A RASs are observed in > 75% of patients following treatment failure[ 10 , 23 - 25 ]. Most of these patients with failure to NS5A inhibitor-containing regimens harbor isolates with NS5A RASs > 100X[ 24 , 26 ].…”
Section: Ns5a Rassmentioning
confidence: 99%